Hubungan Sikap, Pengetahuan dan Motivasi Dengan Kinerja Perawat dalam Pendokumentasian Asuhan Keperawatan di Ruang Anggrek dan Teratai RSUD Kota Bekasi Provinsi Jawa Barat - Aisyiah Aisyiah; Yarni Yarni; Nova Angginy (Jurnal Persada Husada Indonesia, 2015)
Performance is the result achieved by a person under the applicable workload for the job. Nurse performance is the work behavior displayed by someone based on the motivation and behavior of a nurse. This study aims to determine the relationship between attitudes, knowledge, and motivation with the Nurse performance in nursing care documentation at the Orchid and Lotus Room in Bekasi Regional Hospital, West Java Province in 2015. The design used in this study was cross sectional method. The population in this study was the nurses at the Orchid and Lotus Room in Bekasi Regional Hospital totaling 41 people, and all the population sampled in this study (total sampling). The analysis results shows significant relationship between attitudes (p value: 0.019) and motivation (p value: 0.005) with the Nurse performance in nursing care documentation in the Orchid Lounge and Lotus Room in Bekasi Regional Hospital, West Java Province Year 2015. It is expected to nurses in order to better focus and right in doing nursing care documentation, and continues to maintain the attitude and motivation to improve nursing care services to patients.